Generation Z's Perspective On Interest In Buying Fashion Products Through Social Media And The Tiktok Application - Ayu Dwi Astuti; Abriandi Abriandi; Virgo Simamora (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The increased Internet penetration has become a major impetus in increasing the use of e-commerce platforms for online sales. This research is an explanation that aims to find out how social media and Tiktok influence Generation Z's buying interest in shopping fashion products online at DKI Jakarta. The entire Generation Z in the region who used social media and Tiktok to shop for fashion products at least 3 times became the population of this study, with the total number of respondents 208 being selected through the use of purposive sampling techniques. The data collection was carried out with the distribution of Google Forms as one of the forms of questionnaires in DKI Jakarta, and analyzed using SmartPLS 3.0 Partial Least Squares Structural Equation Modeling. (PLS-SEM). The results are proof that social media and Tiktok have a positive and significant influence on Generation Z's buying interest in buying fashion products online.